The dynamics of preferential host switching: Host phylogeny as a key predictor of parasite distribution*. (18th March 2019) - Engelstädter, Jan; Fortuna, Nicole Z.
Abstract: Parasites often jump to and become established in a new host species. There is much evidence that the probability of such host shifts decreases with increasing phylogenetic distance between donor and recipient hosts, but the consequences of such preferential host switching remain little explored. We develop a computational model to investigate the dynamics of parasite host shifts in the presence of this phylogenetic distance effect. In this model, a clade of parasites evolves on an evolving clade of host species where parasites can cospeciate with their hosts, switch to new hosts, speciate within hosts or become extinct. Our model predicts that host phylogenies are major determinants of parasite distributions across trees. In particular, we predict that trees consisting of few large clades of host species and those with fast species turnover should harbor more parasites than trees with many small clades and those that diversify more slowly. Within trees, large clades are predicted to exhibit a higher fraction of infected species than small clades. We discuss our results in the light of recent cophylogenetic studies in a wide range of host–parasite systems.